Interwar Lithuania’s Political and Cultural Life in Tadeusz Katelbach’s Articles and Reports: Review of: Tadeusz Katelbach: atvirai ir slaptai apie Lietuvos politiką. I tomas, Atvirai / sudarytojai Marek Jabłonowski, Andrius Vaišnys, Ingrida Veliutė; iš lenkų k. vertė Biruta Mikalonienė, A. Vaišnys; įžanginio straipsnio (Lietuvos politika ir kultūra Tadeuszo Katelbacho pranešimuose) autoriai M. Jabłonowski, A. Vaišnys. Vilnius: Lietuvos nacionalinė Martyno Mažvydo biblioteka, 2023. – 456 p. ISBN 978-609-405-242-2; Tadeusz Katelbach: atvirai ir slaptai apie Lietuvos politiką. II tomas, Slaptai / sudarytojai Marek Jabłonowski, Andrius Vaišnys, Ingrida Veliutė; iš lenkų k. vertė Biruta Mikalonienė, A. Vaišnys. Vilnius: Lietuvos nacionalinė Martyno Mažvydo biblioteka, 2023. – 388 p. ISBN 978-609-405-242-3-9 (Relevant Tomorrow / Aktualu rytoj, 2022)
The review discusses a two-volume publication, Tadeusz Katelbach: atvirai ir slaptai apie Lietuvos politiką [Tadeusz Katelbach: Open and Secret Reports on Lithuanian Politics], the first publication in Lithuanian of the journalism of Tadeusz Katelbach (1897-1977), a Polish public and political figure, diplomat, journalist and intelligence officer, who worked in Lithuania from 1934 to 1937, as well as of his secret reports to the Polish Ministry of Foreign Affairs about difficult political choices, Lithuanian-Polish relations, the question of Vilnius and the capital of Lithuania, the Lithuanian army, economy and diplomacy. The first volume of the publication contains an introducton by Marek Jabłonowski and Andrius Vaišnys, and articles and correspondence by Katelbach published in Gazeta Polska in 1934-1937. The second volume are secret reports kept in the Archive of New Records in Warsaw. This publication is significant in understanding both the domestic political and cultural life of Lithuania and the relations between Lithuania and Poland in the 1930s.
Keywords: Tadeusz Katelbach; Lithuanian-Polish relations; history of diplomacy in the early 20th century; history of the Central Eastern Europe